2020
DOI: 10.1002/jeq2.20034
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of the antimicrobials lincomycin, chlortetracycline, and sulfamethazine in prairie wetlands

Abstract: Antimicrobials used in livestock production can be present in manure via excretion in the feces and/or urine. Application of raw or processed (composted or stockpiled) manure to crop and pasture land as a plant nutrient source can result in antimicrobial transport to surface waters via rainfall or snowmelt runoff. Little is known regarding antimicrobial persistence in aquatic ecosystems. Consequently, dissipation of environmentally relevant concentrations of three veterinary antimicrobials (lincomycin, chlorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
6
1
Order By: Relevance
“…The half‐life of CTC‐enol in the present laboratory study (4.8 h) is shorter than the DT 50 value of 3.3 d reported by Cessna et al. (2020) for the field study dissipation of CTC in a prairie wetland. Two factors may have played a role in the more rapid dissipation of CTC‐enol in the laboratory study.…”
Section: Resultscontrasting
confidence: 67%
See 3 more Smart Citations
“…The half‐life of CTC‐enol in the present laboratory study (4.8 h) is shorter than the DT 50 value of 3.3 d reported by Cessna et al. (2020) for the field study dissipation of CTC in a prairie wetland. Two factors may have played a role in the more rapid dissipation of CTC‐enol in the laboratory study.…”
Section: Resultscontrasting
confidence: 67%
“…Using liquid chromatography–tandem mass spectrometric analysis, Cessna et al. (2020) suggested that the formation of such complexes may have contributed to the low recovery via solid‐phase extraction of CTC from fortified natural wetland water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, phytoremediation of VAs from animal liquid waste has shown to be promising (Hu et al 2020 ). Cessna et al ( 2020 ) reported DT 50 (time required for 50% dissipation) values of 3.3 d for CTC, 7 d for SMZ, and 14 d for LIN for Canadian prairie wetlands. However, in our study, apart from CTC, none of the other VAs (SMZ, TYL, MON, LIN, ERY, TC) showed evidence of removal in the CW, with no significant difference between concentrations in catch basin vs. retention ponds/wetland samples.…”
Section: Resultsmentioning
confidence: 99%